2015
DOI: 10.1007/s00213-015-4133-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel acetylcholinesterase inhibitor and calcium channel blocker SCR-1693 improves Aβ25–35-impaired mouse cognitive function

Abstract: All these findings indicated that SCR-1693, as a double-target-direction agent, is a considerable candidate for AD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Interestingly, Morris water maze test, plus maze test and different biochemical analysis, demonstrated the restoration of normal learning and memory functions. Moreover, SCR-1693 (a nonselective calcium channel blocker) has been described to attenuate A β 25–35 -induced death in SH-SY5Y cells and to regulate A β -induced signal cascade in neurons [ 58 60 ]. However, the use of calcium channel blockers to mitigate AD outcomes is still much debated.…”
Section: Calcium and Admentioning
confidence: 99%
“…Interestingly, Morris water maze test, plus maze test and different biochemical analysis, demonstrated the restoration of normal learning and memory functions. Moreover, SCR-1693 (a nonselective calcium channel blocker) has been described to attenuate A β 25–35 -induced death in SH-SY5Y cells and to regulate A β -induced signal cascade in neurons [ 58 60 ]. However, the use of calcium channel blockers to mitigate AD outcomes is still much debated.…”
Section: Calcium and Admentioning
confidence: 99%
“…It also inhibited the generation and release of Aβ in cells. Zhang et al, reported its concentration dependent selective, reversible and noncompetitive inhibitor of AChE, (IC 50 = 680 nM) but not BChE in vitro and in vivo [86]. It inhibited all four types of calcium channels at 10 μM concentration non-selectively and reduced Aβ 25-35 -induced SH-SY5Y cell death with higher efficacy than donepezil.…”
Section: Tacrine Analogsmentioning
confidence: 99%
“…It was also better than donepezil and memantine in improving the Aβ 25-35 -induced long-term and short-term learning memory impairment in animal model. It provided protection against glutamate excite toxicity, neuronal damage and Aβ neurotoxicity which indicated that it is a potential lead molecule for AD treatment [86]. The analog 44 incorporating N,N-dimethylene side chain and fluorination at cyclohexane ring of tacrine moiety in analog 43 also showed still higher AChE inhibitory activity (IC 50 = 45nM) than 43 with moderate calcium ions channel blocking property (57.2% at 50,000 nM) [84].…”
Section: Tacrine Analogsmentioning
confidence: 99%
“…Commercial products of donepezil are primarily available as conventional oral dosage forms such as tablets and capsules [8,9]. AD patients need to take the tablet or capsule once a day [10].…”
Section: Introductionmentioning
confidence: 99%